Analisa Ekonomi Atas Hukum Pidana terhadap Penanggulangan Tindak Pidana Korupsi - Dedy Syaputra (Universitas Batanghari Jambi, 2019)
Life in the community will not be far from economic problems, so even economic problems will become a legal problem if the aspect of fulfilling daily needs suffers. Then criminal problems will arise such as theft, and others. Even on a larger scale can the white collar crime arise. The purpose of this study aims to analyze economics of law, or commonly known as